The undrained shear strength of soft clay reinforced with 6mm and 10 mm diameter of group bottom ash column - Raja Nur Shahira, Raja Sharudin (2014)
Soft clay soil can be categorized as problematic soil. A constructing structure which is constructed on a poor ground such as soft clay can affect the stability and settlement of the structure. Soft clay consists of a low shear strength, low ability permeability and high compressibility characteristic and that are the major reasons why a careful design analysis could be taken for any structure built on it. There are various method that been approach to improve the strength of the soft clay soil and the most popular method that is being used in the construction field is stone column. In another view, large production of bottom ash from coal burning in Malaysia has resulted in waste problem. This study is to present suitability in terms of shear strength by using bottom ash to replace sand or stone in columns for ground improvement technique using the laboratory scale model. As we know that sand is one of the non-renewable materials so by utilize by-product or waste which is bottom ash, we can reduce utilization of sands and at the same time we can prevent pollution and sand from disposing. The first stage is to determine the physical and mechanical properties, the test that is being conducted to determine these terms are Atterberg limits, specific gravity, direct shear test, constant head permeability test, standard compaction test and hydrometer test. Kaolin is used as soil sample and bottom ash as the reinforced columns. In the second stage of the study, consolidated kaolin as soft clay were reinforced with group of 3 bottom ash columns and tested for shear strength using Unconfined Compression Test.